Titlepage of "Das Kapital", first edition, 1867, Verlag Otto Meissner Hamburg. Compare BG B2/991 (1867)
Titlepage of "Das Kapital", first edition, 1867, Verlag Otto Meissner Hamburg. Compare BG B2/991.